Quality of Business Environment of the SME: A Sectoral View - Jan Dvorsky; Jaroslav Belas; Ivana Novotna; Martin Fero; Zora Petrakova (Communications - Scientific letters of the University of Zilina, 2020)
The aim of the article is to find out differences in the perception of selected factors that determine the business environment among selected groups of small and medium-sized enterprises (SMEs), divided according to the sector of the national economy they belong to. The first group included SMEs from the sector of transport and services. The second group included SMEs from the construction, manufacturing and agriculture sectors. The questionnaire was completed by 459 SMEs in the Czech and the Slovak Republics. To evaluate the formulated hypotheses, the Chi-square test and the Z-score were used. The case study showed interesting findings. The SMEs in transport and services perceive the competitive environment as more acceptable than the SMEs in construction, manufacturing and agriculture. In addition, the SMEs in transport and services are of the opinion that customers accept prices of their products and services to a greater extent than the SMEs in construction, manufacturing and agriculture. There are also significant differences between selected groups of SMEs in assessing the quality of the judicial system in commercial law and the view that the current level of macroeconomic indicators supports entrepreneurship and creates interesting business opportunities. The national economy sector is not an important criterion in assessing financing, the family environment, R&D infrastructure, the quality of the business environment or the quality of education. The paper brings interesting findings and new incentives for small and medium-sized enterprises; for organizations supporting the business environment; for further research and discussion on the cross-sectoral assessment of the business environment quality and its important factors.